Studi Kelayakan Finansial Usaha Ternak Puyuh Petelur di Desa Serdang Kecamatan Tanjung Bintang Kabupaten Lampung Selatan (Wahana Peternakan, 2018)
ABSTRACTThe quail is one of the poultry producing eggs and meat. Its existence can be as supporting the availability of cheap animal protein. However, the price of quail eggs is relatively fluctuating. The existence of price fluctuations will affect the income of breeders therefore it is of course fluctuating the price should be a concern for businessmen to conduct financial feasibility analysis of the business, so as to make the efficiency of quail cultivation business layer. So this study aims to analyze the financial feasibility of quail farming business in Serdang Village, Tanjung Bintang Subdistrict, South Lampung. This research uses quantitative descriptive method by collecting primary data through direct interview and survey as well as secondary data obtained from various literatures. Then the analysis used in this study is the analysis of the calculation of investment (capital), analysis of production costs, sales revenue analysis, profit and loss analysis, R/C ratio, break even point, and payback period analysis. The conclusion of this research is the business of quail cattle is feasible. This is shown from the results of feasibility analysis using r/c Ratio and break event point analysis which is earned value > 1 and break event point production and price actual production value and price which means the business is profitable.Keywords: Quail, Financial Study, Business Feasibility